Dexmedetomedine-Ketamine versus Propofol-Ketamine as anaesthetic agents in paediatric cardiac catheterization (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Anaesthesia for these patients undergoing for interventional procedures in paediatric patients with congenital cardiac anomalies remains a challenge for the anaesthesiologist. There are no specific techniques to follow and anaesthetic procedure is modified according to the cardiac anomalies, clinical condition of the patients and the cardiologists requirements. Basically the anaesthesiologist can either provide sedation or general anaesthesia. Objective: The aim of this study was to compare the sedation level, haemodynamic effects and recovery patterns in paediatric patients undergoing sedation for cardiac catheterization either with dexmedetomidine-ketamine or propofol-ketamine combination. Materials & Methods: Sixty patients between the ages of 1 to 12 years were scheduled for cardiac catheterization at Cardiac Catheterization Laboratory of Narayana Hrudayalaya Institute of Medical Sciences, Bangalore, India for a period of six months (April to September 2012) for evaluation and intervention of congenital heart disease. Patients were randomly divided into 2 groups of 30 each. All patients were premedicated with intravenous midazolam (0.05mg/kg upto 2 mg) and glycopyrrolate (10 ?g/kg) 5 minutes before the procedure and anaesthesia was induced with ketamine 1mg/kg. The dexmedetomidine-ketamine group (group D, n=30), received dexmedetomidine 1?g/kg over 10 minutes. 19 JAFMC Bangladesh. Vol 10, No 1 (June) 2014 Propfol-ketamine group (group P, n=30) received 50?g/kg/min of propofol by infusion. Heart rate (HR), Systolic Blood Pressure ( SBP), Diastolic Blood Pressure (DBP), Mean Arterial Pressure (MAP), peripheral oxygen saturation (SpO2), respiratory rate (RR), and modified Steward score of all patients was recorded at baseline, after induction and every 10 minutes thereafter. The time to reach a modified Steward score of >or=6 was recorded. Results: Recovery time was significantly less in group P (mean 39±12.32mins) than in group D (mean 48±15.15mins). Statistical significant difference (p